Development of Interactive Multimedia using Lectora inspire for Vehicle Body Construction Courses in Universitas Sriwijaya - Imam Syofii; Dewi Puspita Sari (Journal of Mechanical Science and Engineering, 2020)
This study aims to developing interactive multimedia using Lectora inspire for vehicle body construction courses for Universitas Sriwijaya students. The Lectora inspire software was used because easy to operate and can be made interactive electronic learning. Research and development method were used because it is an effective for developing multimedia and able to test the effectiveness of the product. Based on results, the interactive multimedia using Lectora inspire software are valid with percentage of 87.5% for multimedia and 86.9% for matters, practice with percentage in small group test of 85.52% and field test of 86.61%, and effective because based on post-test results 80% of respondents was passed. Thus, interactive multimedia using Lectora inspire software for vehicle body construction courses proper to use in Mechanical Engineering Education study program, Universitas Sriwijaya.